A companion to reality television - Ouellette, Laurie (Wiley-Blackwell, 2014)
"International in scope and more comprehensive than existing collections, A Companion to Reality Television presents a complete guide to the study of reality, factual and nonfiction television entertainment, encompassing a wide range of formats and incorporating cutting-edge work in critical, social and political theory"--